2004
DOI: 10.1111/j.1525-1497.2004.30635.x
|View full text |Cite
|
Sign up to set email alerts
|

Fostering professionalism in medical education

Abstract: Increasing attention has been focused on developing professionalism in medical school graduates. Unfortunately, the culture of academic medical centers and the behaviors that faculty model are often incongruent with our image of professionalism. The need for improved role modeling, better assessment of student behavior, and focused faculty development is reviewed. We propose that the incentive structure be adjusted to reward professional behavior in both students and faculty. The third-year medicine clerkship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…Evaluation of professionalism must be integrated into assessment and faculty development programs for students and teachers, respectively (Byszewski et al, ). The future of professionalism in medicine can be established by carrying out the assessment of professionalism, and by offering incentives in the form of weightage in grading for students, and professional awards for faculty (Shrank et al, ). However, caution has been urged in grading or evaluating professionalism solely on the basis of behavior, as the attitude underlying behavior might not be predictive given the rewards meted out to professional behavior (Rees and Knight, ).…”
Section: Discusssionmentioning
confidence: 99%
“…Evaluation of professionalism must be integrated into assessment and faculty development programs for students and teachers, respectively (Byszewski et al, ). The future of professionalism in medicine can be established by carrying out the assessment of professionalism, and by offering incentives in the form of weightage in grading for students, and professional awards for faculty (Shrank et al, ). However, caution has been urged in grading or evaluating professionalism solely on the basis of behavior, as the attitude underlying behavior might not be predictive given the rewards meted out to professional behavior (Rees and Knight, ).…”
Section: Discusssionmentioning
confidence: 99%
“…While regulations exist, the way issues have been handled seems only to make the community think that professionalism is not taken seriously because the regulatory bodies appear to protect the doctors rather than look at the interests of the public. Furthermore, regulation, as practiced in other jurisdictions, not only includes penalizing unethical behaviors when they occur but also regular assessment of the clinicians' skills (20). The regulatory bodies play a critical role in ensuring those who are admitted are qualified, their teaching is up to date, and the final assessment is of quality (20).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, regulation, as practiced in other jurisdictions, not only includes penalizing unethical behaviors when they occur but also regular assessment of the clinicians' skills (20). The regulatory bodies play a critical role in ensuring those who are admitted are qualified, their teaching is up to date, and the final assessment is of quality (20). Improvement of the educational environment was suggested as one of the ways in which individuals could build an educational community.…”
Section: Discussionmentioning
confidence: 99%
“…If he believes this, he has failed to educate himself regarding the evidence. Research has unequivocally shown that creating a hostile, intimidating environment is antithetical to learning skills and professionalism [3,4]. So, if Dr. Powell believes he is a good instructor, he has failed to approach his duty as a teacher with the same evidence-based methods that he presumably applies to his specialty.…”
Section: Commentarymentioning
confidence: 99%